2018
DOI: 10.3389/fmicb.2018.02386
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrosomonas europaea MazF Specifically Recognises the UGG Motif and Promotes Selective RNA Degradation

Abstract: Toxin-antitoxin (TA) systems are implicated in prokaryotic stress adaptation. Previously, bioinformatics analysis predicted that such systems are abundant in some slowly growing chemolithotrophs; e.g., Nitrosomonas europaea. Nevertheless, the molecular functions of these stress-response modules remain largely unclear, limiting insight regarding their physiological roles. Herein, we show that one of the putative MazF family members, encoded at the ALW85_RS04820 locus, constitutes a functional toxin that engende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Subsets of toxins sharing similar target sequences are boxed with different colors. Protein identifiers and cleavage specificity were taken from: E. coli MazF (ChpAK) (NP_417262.1) (Culviner and Laub, 2018;Mets et al, 2019), ChpBK (NP_418646.1) (Zhang et al, 2005), Kid (PemK) (YP_003937673.1) (Munoz-Gomez et al, 2004;Zhang et al, 2004); Bacillus subtilis MazF bs (AOR96854.1) (Park et al, 2011); Bacillus anthracis MoxT (NP_842807.1) (Verma and Bhatnagar, 2014); Staphylococcus aureus MazF sa (BBJ19047.1) (Zhu et al, 2009); Staphylococcus equorum MazF seq (AFV93478.1) (Schuster et al, 2013); Clostridium difficile MazF cd (YP_001089981.1) (Rothenbacher et al, 2012); Legionella pneumophila MazF lp (CCD10720.1) (Shaku et al, 2018); Deinococcus radiodurans MazF DR0417 (AAF09995.1) (Miyamoto et al, 2017); Haloquadratum walsbyi MazF hw (WP_048066888.1) (Yamaguchi et al, 2012); Pseudomonas putida MazF pp (NP_742932.1) (Miyamoto et al, 2016a); Myxococcus xanthus MazF mx (SDX28280.1) (Nariya and Inouye, 2008); Methanohalobium evestigatum MazF me (WP_013195679.1); Nitrosomonas europaea MazF ne1 (WP_011111532.1) (Miyamoto et al, 2018), MazF NE1181 (CAD85092.1) (Miyamoto et al, 2016b); Mycobacterium tuberculosis MazF-mt1 (NP_217317.1) (Zhu et al, 2006), MazF-mt3 (NP_216507.1) (Zhu et al, 2008;Schifano et al, 2014), MazF-mt6 (NP_215618.1) (Schifano et al, 2013), MazF-mt7 (NP_216011.1) (Zhu et al, 2008), MazF-mt9 (YP_004837055.2) (Barth et al, 2019).…”
Section: Mazf Toxinsmentioning
confidence: 99%
“…Subsets of toxins sharing similar target sequences are boxed with different colors. Protein identifiers and cleavage specificity were taken from: E. coli MazF (ChpAK) (NP_417262.1) (Culviner and Laub, 2018;Mets et al, 2019), ChpBK (NP_418646.1) (Zhang et al, 2005), Kid (PemK) (YP_003937673.1) (Munoz-Gomez et al, 2004;Zhang et al, 2004); Bacillus subtilis MazF bs (AOR96854.1) (Park et al, 2011); Bacillus anthracis MoxT (NP_842807.1) (Verma and Bhatnagar, 2014); Staphylococcus aureus MazF sa (BBJ19047.1) (Zhu et al, 2009); Staphylococcus equorum MazF seq (AFV93478.1) (Schuster et al, 2013); Clostridium difficile MazF cd (YP_001089981.1) (Rothenbacher et al, 2012); Legionella pneumophila MazF lp (CCD10720.1) (Shaku et al, 2018); Deinococcus radiodurans MazF DR0417 (AAF09995.1) (Miyamoto et al, 2017); Haloquadratum walsbyi MazF hw (WP_048066888.1) (Yamaguchi et al, 2012); Pseudomonas putida MazF pp (NP_742932.1) (Miyamoto et al, 2016a); Myxococcus xanthus MazF mx (SDX28280.1) (Nariya and Inouye, 2008); Methanohalobium evestigatum MazF me (WP_013195679.1); Nitrosomonas europaea MazF ne1 (WP_011111532.1) (Miyamoto et al, 2018), MazF NE1181 (CAD85092.1) (Miyamoto et al, 2016b); Mycobacterium tuberculosis MazF-mt1 (NP_217317.1) (Zhu et al, 2006), MazF-mt3 (NP_216507.1) (Zhu et al, 2008;Schifano et al, 2014), MazF-mt6 (NP_215618.1) (Schifano et al, 2013), MazF-mt7 (NP_216011.1) (Zhu et al, 2008), MazF-mt9 (YP_004837055.2) (Barth et al, 2019).…”
Section: Mazf Toxinsmentioning
confidence: 99%
“…It is well known that MazF homologues are widespread across the bacterial and archaeal domains [36]. They cleave single-stranded RNAs at specific three to seven base motifs, thereby modulating translation through degradation of intracellular RNA pools or silencing of specific transcripts (Table S3) [11,15,[17][18][19]26,28,29,31,[37][38][39][40][41][42][43][44][45]. Here, we demonstrated that MazF-nd1 cuts AACU, AACG, and AAUU motifs.…”
Section: Discussionmentioning
confidence: 61%
“…Nitrifying bacteria are generally sensitive to environmental fluctuations and easily enter a dormant state. Previously, we showed the MazF endoribonucleases (referred to as MazF NE1181 and MazFne1 in the previous papers) in N. europaea are functional growth regulators, and their sequence-specificities may allow N. europaea to alter its translation profile and survive under certain stressful conditions [18,19]. MazF-nd1 shares only 34.2% and 23.5% identities with MazF NE1181 and MazFne1, respectively ( Figure S3).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is found also in other clinically important bacteria (Mittenhuber, 1999;Nguyen et al, 2011;Schifano et al, 2013;Cho et al, 2017). Several studies were conducted to characterize the MazEF locus by studying its transcriptional activation and function Fu et al, 2009;Zhu et al, 2009;Zorzini et al, 2011Zorzini et al, , 2014Miyamoto et al, 2018). MazEF is composed of MazF toxin and its activity is modulated by the MazE antitoxin (Figure 1).…”
Section: Introductionmentioning
confidence: 99%